PENERAPAN STRATEGI PEMASARAN DAN AKSESIBILITAS RUMAH TANGGA TERHADAP BIHUN TAPIOKA DI KOTA METRO - Fadhilah Ismi Bazai; Wuryaningsih Dwi Sayekti; Dyah Aring Hepiana Lestari (Lampung University, 2018)
This research aims to study the owner's understanding of marketing strategy of tapioca vermicelli, analyze the implementation of marketing strategy that has been done, and know the accessibility of consumers to obtain tapioca vermicelli. This research used a case study method at Sinar Harapan Agroindustry (SH) and Bintang Obor (BO). Respondents are the owner of agroindustry, distributors, and consumers of tapioca vermicelli. Data are analyzed by a descriptive statistical analysis (level of understanding through an all-round management approach and accessibility of consumers) and qualitative descriptive (the realization of marketing strategy that has been done). The results showed that tapioca vermicelli producers in Metro City are quite understand the marketing strategy, but their implementation is not in accordance with their understanding. The owner of BO understands the importance of marketing strategy more compared to the owner of SH. The implementation of marketing strategy by SH and BO producers are almost the same. The difference of these two agroindustries are that the BO implements the price reserve strategy while SH does not. Accessibility of consumers to obtain tapioca vermicelli is easy. Key words: accessibility, marketing strategy, tapioca vermicelli